Pengembangan Modul Umum Kokurikuler Gaya Hidup Berkelanjutan Menjaga Kesehatan Organ Tubuh Di SDN 34 Pontianak Kota - Artiah, Hikmah Rohoy; Hairida, Hairida; Kartono, Kartono (Jurnal PGSD, 2025)
This research is motivated by the limited studies on the development of co-curricular modules, whereas this phenomenon has a significant impact on the deepening of the material that has been obtained by students in intercurricular activities. The purpose of this study is to produce a valid and feasible general co-curricular module. The method used is Research and Development with the Sugiyono development model, the potential and problem stage, the researcher examines more about the dimensions of the latest graduates so that it is obtained that the dimensions of the latest graduation have never been applied in schools, the information gathering stage, the researcher interviews class 5A teachers of SDN 34 Pontianak City for initial research data, the product design stage, the researcher compiles the design of the developed module, then the validation stage of the developed product design is assessed by language and material experts, and the last stage of design improvements is carried out to reduce the shortcomings obtained from the results of product validity. The results of the validation of the language aspect obtained a value of 88.66 criteria "Eligible with a very good predicate", the results of the validation of the material aspect obtained a result of 91.33 criteria "Eligible with a very good predicate" and the results of teacher responses obtained the category "very good" from 3 teachers and the category "good" from 1 teacher.